2003
DOI: 10.1124/jpet.103.049254
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Characterization of the Novel Histamine H3-Receptor Antagonist N-(3,5-Dichlorophenyl)-N′-[[4-(1H-imidazol-4-ylmethyl)phenyl]-methyl]-urea (SCH 79687)

Abstract: We present the pharmacological and pharmacokinetic profiles of a novel histamine H 3 receptor antagonist, N- (3,phenyl]-methyl]-urea (SCH 79687). The H 3 -receptor binding K i values for SCH 79687 were 1.9 and 13 nM in the rat and guinea pig (GP), respectively. The K i values for SCH 79687 at histamine H 1 and H 2 receptors were greater than 1 M. SCH 79687 showed a 41-and 82-fold binding selectivity for the H 3 receptor over ␣ 2A -adrenoceptors and imidazoline I 2 , and Ͼ500-fold H 3 selectivity compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In animal models, H 3 receptor antagonists have been shown to enhance attentive and cognitive behaviors, to enhance wakefulness, and when coadministered with H 1 antagonists to act as nasal decongestants . The molecular mechanisms whereby H 3 antagonists induce these effects are indirect and probably mediated by the enhanced release of neurotransmitters such as histamine, acetylcholine, dopamine, and others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal models, H 3 receptor antagonists have been shown to enhance attentive and cognitive behaviors, to enhance wakefulness, and when coadministered with H 1 antagonists to act as nasal decongestants . The molecular mechanisms whereby H 3 antagonists induce these effects are indirect and probably mediated by the enhanced release of neurotransmitters such as histamine, acetylcholine, dopamine, and others.…”
Section: Introductionmentioning
confidence: 99%
“…Two newer imidazole-based compounds, GT-2331 ( 5 ) and SCH-79876 13b ( 6 ), have also been described in the literature as potent H 3 receptor antagonists. Compound 6 , in combination with an H 1 antagonist, was active as a nasal decongestant in a feline model at 3−10 mg/kg 13a 1 Structures of histamine ( 1 ), imidazole-based H 3 antagonists 2 − 6 , and non-imidazole H 3 antagonists 7 − 13 . …”
Section: Introductionmentioning
confidence: 99%
“…H 3 receptor antagonists showed ability to inhibit nasal congestion in combination with antihistamines that target the H 1 receptor [18]. Combined therapy by SCH 79687 (H 3 R antagonist) and loratadine (H 1 R antagonist) showed anti-allergic and decongestant properties [19]. In other studies, combined therapy by PF-03654746 (H 3 R antagonist) and fexofenadine (H 1 R antagonist) in patients with AR led to suppression of all nasal symptoms induced by allergen [20] [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, observations from a preclinical model of nasal congestion (NC) showed that H3Rs along with H1Rs participated in the histamine-induced NC and demonstrated the sense of simultaneously blocking both H1 and H3 receptors in conditions with NC [67, 68]. Also, compound SCH-79687 is a highly potent H3R antagonist that reduced congestion in animal models of AR when co-administered with a H1R antagonist [69]. This supports the hypothesis that the efficacy of H3R antagonists is related to peripherally mediated release of norepinephrine from nasal mucosal H3 receptors, because SCH-79687 virtually does not penetrate the brain [70].…”
Section: Histamine H2 H3 and H4 Receptors And Their Propertiesmentioning
confidence: 99%